INTERVENSI PENINGKATAN MUTU PELAPORAN INDIKATOR KINERJA PENGGUNAAN OBAT RASIONAL (POR) DI KABUPATEN KARAWANG - Yusrianti; Erna Kristin (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2021)
Background: Rational use of drugs plays a role in reducing morbidity and mortality in the community associated with the treatment of disease. Acute respiratory infections (ARI), diarrhea, and myalgia are diseases that are still commonly found and treated in primary health centers, so far the three diagnoses are considered potential for irrational treatment. Data from existing reports can actually be used to identify the rationality of rational drug use, but until now the quality of report data is still poor. Therefore, how interventions can improve the quality of reporting the performance indicators of rational drug use in the Karawang District. Objective: To improve the quality of reporting on performance indicators of rational drug use (POR) in Karawang District. Methods: This study used a Quasi-Experimental research design with one- group pretest-posttest design, without a comparison group (control), in Karawang District in January - March 2020. Twenty officers reporting rational drug use in primary health centers were selected by purposive sampling. Results: Training interventions can improve the quality of reporting the performance indicators of rational drug use from the results of increased pretest after the training intervention (posttest) namely; report preparation process 25% to 80%, report completeness from 45% to 95%, timeliness from 15% to 75%, report compliance with technical instructions from 0% to 75%. Conclusion: Providing interventions in the form of explanations of technical guidelines for rational drug use and training has been proven to improve the quality of reporting on performance indicators of rational drug use.